1997
DOI: 10.1006/viro.1997.8857
|View full text |Cite
|
Sign up to set email alerts
|

Equine Herpesvirus 1 Mutants Devoid of Glycoprotein B or M Are Apathogenic for Mice but Induce Protection against Challenge Infection

Abstract: Equine herpesvirus 1 (EHV-1) mutants devoid of the open reading frames (ORFs) of either glycoprotein (g) B or M were constructed and tested for their immunogenic potential in a murine model of EHV-1 infection. The mutant viruses were engineered using the virulent EHV-1 strain RacL11 or the modified live vaccine strain RacH by inserting the Escherichia coli LacZ gene into the viral ORFs. RacL11-infected mice showed signs typical of an EHV-1 infection, whereas mice infected with the EHV-1 gB- or gM-negative muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…4B). From the results we concluded that EHV-1 is able to transduce human PBMC expressing various CD molecules on their cell surface after stimulation with ConA using less than 1 IU, i.e., 100 virus particles per cell (37).…”
Section: Ehv-1 Efficiently Delivers a Transgene Into Cells Of Variousmentioning
confidence: 90%
See 2 more Smart Citations
“…4B). From the results we concluded that EHV-1 is able to transduce human PBMC expressing various CD molecules on their cell surface after stimulation with ConA using less than 1 IU, i.e., 100 virus particles per cell (37).…”
Section: Ehv-1 Efficiently Delivers a Transgene Into Cells Of Variousmentioning
confidence: 90%
“…Serial 10-fold dilutions of supernatants were prepared and added to RK13 plated in six-well plates (Falcon), and viruscontaining solutions were replaced with medium containing methylcellulose 2 h p.i. as described earlier (37). Human cell lines were the CD4 ϩ T-cell line MT4 (MRC ARP017), the melanoma cell line MeWo (ATCC HTB-65), the hepatocellular carcinoma cell line Huh7 (ATCC CCL-185), the kidney carcinoma cell line 293T (ATCC CRL-1573), the lung carcinoma cell line H1299 (ATCC CRL-5803), and the cervix carcinoma cell line HeLa (ATCC CCL-2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of gB results in loss of infectivity, as observed in cell culture, and after infection of primary target cells in vivo by phenotypically complemented mutant virus, viral spread does not occur (1,31,33,37). Mutations in the cytoplasmic domain of gB resulting in a syncytial phenotype profoundly influence pathogenesis in vivo (7,10,42,45).…”
Section: Discussionmentioning
confidence: 99%
“…Together, these data argue that gM almost certainly has an important role in the infectious cycle of herpesviruses and that the function of this protein may only be observable under more stringent conditions of replication such as occur in vivo. In fact, attenuation has been noted after infection of animals with viruses lacking gM and/or gN (9,26,30). The contribution of gN to the function(s) of gM is unknown.…”
mentioning
confidence: 99%